Risk profile of postnatal women and their babies attending a rural district hospital in South Africa - Rees, Kate; Mutyambizi, Chipo; Ndou, Rendani; Struthers, Helen E; McIntyre, James A; Dunlop, Jackie (Frontiers in Global Women's Health, 2022)
Background Maternal and neonatal mortality remain unacceptably high and inequitably distributed in South Africa, with the postnatal period being a dangerous time for both mother and baby. The aim of this paper is to describe the risk factors for poor postnatal outcomes, including postnatal mental health disorders, in a population of postnatal women and their babies utilising rural district hospital services in Limpopo Province, with a focus on HIV. We also describe health care provider compliance with relevant guidelines. Methods All women discharged from the postnatal ward of the district hospital who consented to participate were enrolled. A research nurse used a structured questionnaire to collect data about sociodemographic information, pregnancy and pre-existing conditions, complications during labour and birth, pregnancy outcomes and mental health risk factors. Results The questionnaire was completed for 882 women at the time of discharge. Only 354 (40.2%) of participants had completed secondary education, and 105 (11.9%) reported formal employment. Chronic hypertension was recorded in 20 women (2.3%), with an additional 49 (5.6%) developing a hypertensive disorder during pregnancy. HIV prevalence was 22.8%. 216 women (24.5%) had a mental health risk factor, with 40 reporting more than one (4.5%). Having no income, no antenatal care, having HIV and any hypertensive disorder were significantly associated with a positive mental health risk screen in multivariable analysis. There were 31 stillbirths and early neonatal deaths (3.5%), and 119 babies (13.4%) were born at a low birth weight. Stillbirth or early neonatal death was significantly associated with no antenatal care in multivariable analysis. Conclusions Women and babies in this study experienced multiple risk factors for poor outcomes in the postpartum period. Improved postnatal care coverage delivered through innovative models throughout the 6-week postnatal period should be emphasized as a critical strategy to protect mothers and babies. Tools to identify mothers and babies at risk of postnatal complications would allow limited resources to be allocated where they are most needed.